A comprehensive review on nanocellulose-based membranes : methods, mechanism, and applications in wastewater treatment - Ain Zaienah, Sueraya; Md Rezaur, Rahman; Devagi, Kanakaraju; Khairul Anwar, Mohamad Said; Anthonette, James; Al-Khalid, Othman; Muhammad Khusairy, Bakri; Jamal, Uddin (Springer Nature, 2023)
As the demand for clean water sources increases, it is crucial to identify the best wastewater treatment technology that is cost-effective and energy efficient. Despite their separation performance and durability limitations due to the membrane materials and chemicals used in current production techniques, membranes are useful for recovering water from contaminated water sources. This review focuses on nanocellulose-based membranes that utilize various methods, as biodegradable and inexpensive nanocellulose has been used widely in membrane research in recent years. The research regarding nanocellulose-based membranes is growing widely as incorporating nanocellulose enhances the hydrophilic properties and mechanical strength and increases the membrane adsorption capacities, which is ideal for future commercialization. The material high aspect ratio explains this potential, large specific surface area, good capacity retention, and environmental inertness. In addition to the benefits already described, active sites include chemical moieties that might improve the efficacy of pollutants attaching to surfaces. Besides that, nanocellulose could be chemically modified to increase the surface affinity and reactivity of membranes to remove specific contaminants efficiently. Future research directions for lignocellulosic nanocellulose for wastewater treatment and the difficulties and possibilities of nanocellulose-based membranes in these fields are also discussed. Lastly, the application of nanocelluloses in water treatment with an emphasis on membranes and filters fabricated primarily of nanocellulose. Hence, nanocellulose for these membrane applications provides tremendous potential for the wastewater treatment industry.